Double-Balloon Endoscopy Theory and Practice - Sugano, K.; Yamamoto, H.; Kita, H.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2006)
Endoscopic access to the small intestine has for a long time presented a challenge to physicians. Although capsule endoscopy can provide an endoscopic image from the entire small intestine, neither biopsy nor endoscopic treatment can be performed with it. In order to make more definitive diagnoses of abnormal findings detected by capsule endoscopy, a new system incorporating greater insertability and maneuverability is required. Double-balloon endoscopy, which enables endoscopic observation of the entire small intestine, represents such a new system. The chapters of this book describe the principles, insertion technique, and clinical applications of double-balloon endoscopy, which will become the gold standard of enteroscopy and may well eliminate the need for intraoperative enteroscopy in many patients. As such, this book will provide an invaluable source of reference for all practitioners working in the field.
What Is a Double-Balloon Endoscope?- Equipment -- Indications, Contraindications, and Preoperative Examination -- Informed Consent -- Principle of Insertion and Characteristics -- Preparation and Premedication -- Preparation of Devices -- Specific Procedures for Insertion -- Expected Complications and Procedures to Address the Complications -- Endoscopic Diagnosis -- Diagnosis -- Small-Intestinal Tumor -- Stenosis of the Small Intestine -- Intestinal Ulcers and Erosions -- Postoperative Intestinal Lesions -- Vascular Disease -- Endoscopic Treatment -- Characteristics and Techniques of Endoscopic Treatment -- Hemostasis -- Polypectomy and Endoscopic Mucosal Resection -- Balloon Dilatation and Stenting -- Other Applications -- Double-Balloon Endoscopy as Colonoscopy -- Use in Patients with Previous Intestinal Surgery -- Removal of Foreign Bodies from the Small Intestine.
Keywords: Gastroenterology .; Minimally invasive surgery; Gastroenterology; Minimally Invasive Surgery